The economics of flue gas cooling technology for coal-fired power stations with flue gas desulfurisation - Roberts, Pierru; Els, C. J. Luther; Bosyi, Oleg; Kornelius, Gerrit (Clean Air Journal, 2018)
Developments in heat exchanger technology, specifically in the use of polymers as tube material, have allowed the use of gas to water heat exchangers under conditions previously not viable. Two applications in the flue gas cleaning circuit of coal-fired power stations are described in this paper. In conventional pulverised coal-fired boilers, cooling of gas prior to the wet flue gas desulfurisation (WFGD) absorber reduces water consumption for evaporative cooling of the flue gas and can recover heat for feed water preheating or for use elsewhere in the plant. In another application, circulating fluidised bed boilers, which are currently proposed for a few independent power producers and may not require wet FGD, heat recovery is still feasible upstream of the bag filter typically used for particulate emission control. The extracted heat can again be recovered for use in other power plant processes, in this case most economically for pre-heating combustion air. This paper presents case studies for each of the above applications, showing that the power station efficiency is typically increased by approximately 1% of its pre-installation value. An economic analysis is provided for each, including additional power sales, reduced water consumption, or reduced fuel use with a reduction in carbon tax. For the larger installations with WFGD, payback time can be in the order of 6 years.